2000
DOI: 10.1080/10408360091174303
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid-Associated Ophthalmopathy: Clinical Features, Pathogenesis, and Management

Abstract: Thyroid-associated ophthalmopathy (TAO) is a progressive eye disorder characterized by immune-mediated inflammation of the extraocular muscles and orbital connective tissue. TAO is linked, in a unique way, with thyroid autoimmunity, in particular Graves' hyperthyroidism. Our working hypothesis for the pathogenesis of TAO is that recognition of a thyrotropin receptor (TSHR)-like protein in the orbital preadipocytes by antibodies may be the initial event leading to homing of lymphocytes into the orbital tissues.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 153 publications
0
39
1
Order By: Relevance
“…It is possible that the improvement in the proptosis also had an effect on the amelioration of dry eye symptoms. It has been shown that the improvement of thyroid functions, which results in lowering of intraorbital glycosaminoglycan levels, may resolve the proptosis and palpebral angle widening (8). However, no statistically significant difference was found in the palpebral angle measurements between the three groups.…”
Section: Discussioncontrasting
confidence: 37%
See 2 more Smart Citations
“…It is possible that the improvement in the proptosis also had an effect on the amelioration of dry eye symptoms. It has been shown that the improvement of thyroid functions, which results in lowering of intraorbital glycosaminoglycan levels, may resolve the proptosis and palpebral angle widening (8). However, no statistically significant difference was found in the palpebral angle measurements between the three groups.…”
Section: Discussioncontrasting
confidence: 37%
“…The most common factors are T cell-dependent ocular surface inflammation, increased tear film evaporation and hyperosmolarity due to proptosis, especially in Graves' disease. Additionally, the effect of several inflammatory cytokines such as IL1-α, IL-4, and IGF-1 may play a role in this process (8). Recently, in addition to these factors, thyroid hormone receptors β-1 (Thrb-1), which are located on lacrimal glands, were found to be responsible for the development of dry eye (10).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Infiltration of activated T cells, B cells, and macrophages as well as the expansion of eye muscles and orbital fat tissues can be observed through histologic examinations of the retrobulbar tissues (Weetman et al, 1989). The course of GO is unpredictable and rapid deterioration can occur at any time (Bednarczuk et al, 2007;Yamada et al, 2000). The etiology of GD and GO may be multifactorial, involving complex interactions between genetic, environmental, endogenous and local factors (Farid and Balazs, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Many workers have investigated the possible existence of auto antigens that are expressed in both the thyroid and orbit [5,[13][14][15]. Such antigens include the TSHR [7,8,16], the 64-kDa protein, now identified as the Flavoprotein (Fp) sub-unit succinate dehydrogenase [17] or some other, as yet unidentified, thyroid and eye muscle shared cell membrane antigen.…”
Section: Introductionmentioning
confidence: 99%